Novel management of expected post-radiotherapy complications in hepatocellular carcinoma patients: a case report - Sung Hoon Chang; Tae Suk Kim; Yong Hwan Jeon; Nuri Hyun Jung; Dae Hee Choi (Korean Liver Cancer Association, 2022)
In recent years, radiotherapy (RT) has been used to treat hepatocellular carcinoma (HCC) at each stage. This clinical trend has developed with the increasing improvement of RT techniques, which show clinical results comparable to those of other treatment modalities. Intensity-modulated radiotherapy uses a high radiation dose to improve treatment effectiveness. However, the associated radiation toxicity can damage adjacent organs. Radiation-induced gastric damage with gastric ulcers is a complication of RT. This report presents a novel management strategy for preventing post-RT gastric ulcers. We present the case of a 53-year-old male patient diagnosed with HCC, who experienced gastric ulcer after RT. Before the second round of RT, the patient was administered a gas-foaming agent, which was effective in preventing RT complications.